The responses of white blood cells to weight loss among young male judoists - Shariat, Ardalan; Mohd Tamrin, Shamsul Bahri; Danaee, Mahmoud; Karimi, Hossein (Limited Liability Company, 2013)
The purpose of this study was the assessment of white blood cells in response to acute and gradual weight loss among young male judoists. Material and Methods—Twenty four healthy young judoists aged 17.0±1.2 years (mean ± SD), with one year of experience in judo training, selected and they were randomly classified in two groups of acute weight loss and gradual weight loss. Blood sampling was conducted in three stages: 1) before weight loss, 2) 18 hours after weight loss, and 3) after the last phase of physical exercise performance tests. Results— The average amount of white blood cells in the phase 2 for both groups didn’t increase meaningfully (Acute: P=0. 53, Gradual: P=0.48) but the increase in the phase 3 for both groups was significant (P<0.01). Conclusion— This study concludes that acute weight loss can result in changing the level of white blood cells which are determined in immunity system and related disease.